Esophageal foreign body: Shirdan - Sehmus Olmez; Bunyamin Saritas (Journal of the Pakistan Medical Association, 2021)
Shirdan is a traditional food, common in southern parts of Turkey. It is consumed as a fast food and prepared by cleaning the lamb’s stomach and filling it with spicy rice. We report two cases of atypical foreign bodies (Shirdan) located in the esophagus. In the known literature, Shirdan has not ever been reported as an oesophageal foreign body. Case 1. A 46 years old woman was admitted to the emergency department with dysphagia and drooling shortly after eating Shirdan. As the food was hot, she swallowed it without chewing. An urgent endoscopy was performed which revealed a Shirdan just below the upper esophageal sphincter (Figure 1). Shirdan pieces were pushed into the stomach by the biopsy forceps. Case 2. A 73 years old man presented to the emergency department with dysphagia and chest pain after eating Shirdan. As he did not have enough teeth he ate it without chewing it well. Clinical examination and laboratory tests were normal. An urgent endoscopy showed the Shirdan in the middle esophagus (Figure 2a). Shirdan was removed with a snare. (Figure 2b). At a second-look endoscopy, a stricture was seen at 27 cm away from incisors (Figure 2c). Esophageal foreign bodies (EFB) are seen frequently and they are one of the common causes of urgent endoscopy. Diagnosis and treatment of EFB should be made as early as possible to avoid serious complications, such as perforation. Routine radiological examinations are not always necessary for diagnosis of EFB before endoscopy. Flexible endoscopy is used for both diagnosis and treatment of EFB which can be applied to most patients.1,2 Continuous...